âMASATUN BI HAJMI âAINI AL-FARASIâ DALAM ANTOLOGI CERPEN WARDATUN FI AL-MUâTAQALI AL-KHAYYAMI KARYA JAMAL JUNAID: ANALISIS STRUKTURAL ROBERT STANTON - , ANAKA DL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this research is to reveal the intrinsic elements contained in the short story of âMa>satun bi H}ajmi âAini al-Farasiâ in the stories anthology by Jama>l Junaid and the linkages between each element in creating the storyâs coherence. Therefore, this research uses structural analysis. Intrinsic elements examined in this research are the theme